A literature review of KO standardization in neutron activation analysis - 383368 Syahmi Sapit; Noorddin Ibrahim; Fakulti Sains (2007)
Project Paper (Sarjana Muda Sains (Fizik Kesihatan)) - Universiti Teknologi Malaysia, 2007